2019
DOI: 10.1051/matecconf/201929013003
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insight into teaching profession by using film: a preservice teachers’ experience

Abstract: Films can be used as instructional tools in higher education in different disciplines. In the context of teacher education, films with and about teachers and pupils are valuable resources for learning about the teaching profession. The purpose of this study is to examine the pre-service teachers’ reflections on a film with an educational content and message - The Triumph (The Ron Clark Story, 2006). One research question guided the investigation: What are the students’ cognitive and emotional gains for the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Movies have been used in many various contexts, for example, in Turkey (Elmas et al, 2019;Gezer, 2020;Kaşkaya & Ünlü, 2011;Kontaş, 2016), Israel (Eilam & Poyas, 2009), the United States (Webb & Kapavik, 2017) and in Romania (Cretu, 2019). These studies also investigated pre-service teachers in various learning disciplines, for example, involving pre-service teachers of English (Eilam & Poyas, 2009;Gezer, 2020;Halim et al, 2019), and science, social studies, and mathematics (Cretu, 2019;Elmas et al, 2019;Kaşkaya & Ünlü, 2011;Kontaş, 2016). Several studies reported that movies could prevent pre-service teachers from the reality shock of the future teaching profession (Cretu, 2019;Kaşkaya & Ünlü, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Movies have been used in many various contexts, for example, in Turkey (Elmas et al, 2019;Gezer, 2020;Kaşkaya & Ünlü, 2011;Kontaş, 2016), Israel (Eilam & Poyas, 2009), the United States (Webb & Kapavik, 2017) and in Romania (Cretu, 2019). These studies also investigated pre-service teachers in various learning disciplines, for example, involving pre-service teachers of English (Eilam & Poyas, 2009;Gezer, 2020;Halim et al, 2019), and science, social studies, and mathematics (Cretu, 2019;Elmas et al, 2019;Kaşkaya & Ünlü, 2011;Kontaş, 2016). Several studies reported that movies could prevent pre-service teachers from the reality shock of the future teaching profession (Cretu, 2019;Kaşkaya & Ünlü, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also investigated pre-service teachers in various learning disciplines, for example, involving pre-service teachers of English (Eilam & Poyas, 2009;Gezer, 2020;Halim et al, 2019), and science, social studies, and mathematics (Cretu, 2019;Elmas et al, 2019;Kaşkaya & Ünlü, 2011;Kontaş, 2016). Several studies reported that movies could prevent pre-service teachers from the reality shock of the future teaching profession (Cretu, 2019;Kaşkaya & Ünlü, 2011). Movies were believed to be influential and inspiring (Gezer, 2020;Webb & Kapavik, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations